Purchasing Power Gains on Debt: The Effect of Expected and Unexpected Inflation. - Kaplan, Robert S. (The Accounting Review, 1977)
ABSTRACT: The gain or loss on net monetary assets is a central and controversial feature of general price-level-adjusted financial statements. Highly levered companies will show large purchasing power gains on their debt during inflationary periods even when the inflation is correctly anticipated. In this paper, a model is developed, based on the Fisher effect for the adjustment of interest rates to expected inflation, to show that much of the apparent purchasing power gain on debt is due not to real purchasing power gains but, rather, to the gain associated with the reduction in the market value of debt because of unanticipated inflation. When changes in the market value of outstanding debt are explicitly recognized, a significant part of the GPLA purchasing power gain on debt can be viewed as an offset to nominal interest expense to arrive at the real interest expense for outstanding debt.